1997
DOI: 10.2500/105065897781446801
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nasal Resistance in White Caucasians and Blacks

Abstract: Total nasal resistance was measured in 42 white caucasian and 32 black healthy adults by both anterior and posterior rhinomanometry after using a nasal decongestant. The nasal airway resistance was found to be lower in the blacks compared to the caucasians by both anterior and posterior methods. The mean total nasal airway resistance was 0.136 Pa/ cm3/s in the blacks and 0.179 Pa/cm3/s in the caucasians by the anterior method, and 0.134 Pa/cm3/s and 0.161 Pa/cm3/s, respectively, by the posterior method. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…On the other hand, our normal value is higher than other reported values probably because the nasal resistance was measured in the untreated state. 6,7 2 Cole reported a mean total nasal resistance of 0.33 Pa/cm 3 /s for 800 asymptomatic adults at a transnasal pressure of 150 Pascals. 3 Shelton and Eiser found that in the untreated noses of normal subjects the mean total resistance was 0.31 (ranged from 0.13 to 0.84) Pa/ cm 3 /s at a reference pressure of 75 Pascals and mean unilateral resistance was 0.65 (ranged from 0.25 to 2.4) Pa/cm 3 /s at a reference pressure of 150 Pascals.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our normal value is higher than other reported values probably because the nasal resistance was measured in the untreated state. 6,7 2 Cole reported a mean total nasal resistance of 0.33 Pa/cm 3 /s for 800 asymptomatic adults at a transnasal pressure of 150 Pascals. 3 Shelton and Eiser found that in the untreated noses of normal subjects the mean total resistance was 0.31 (ranged from 0.13 to 0.84) Pa/ cm 3 /s at a reference pressure of 75 Pascals and mean unilateral resistance was 0.65 (ranged from 0.25 to 2.4) Pa/cm 3 /s at a reference pressure of 150 Pascals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above studies, Canbay and Bhatia (57) used rhinomanometry to compared nasal resistance in 42 Caucasians and 32 African Americans; not only that their study found lower mean nasal resistance in African Americans than Caucasians, the differences in values were reported to be statistically significant. Zhu et al (58) used CFD methodology to compare airflow pattern among three subjects from different ethnic descents (Caucasian, Chinese, and Indian), and they concluded that airflow behavior in the main nasal cavity was different between the Caucasian male subject and the Indian male subject.…”
mentioning
confidence: 95%
“…In rhinomanometry, there are published normal ranges of nasal airway resistance for anterior and posterior rhinomanometry [1,23,24]. Some information on the effects of ethnicity on nasal patency is also available [15,25].…”
Section: Normal Valuesmentioning
confidence: 98%